2021
DOI: 10.1002/essoar.10508135.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Speciation and Coordination of a Deep Earth Carbonate-Silicate-Metal Melt

Abstract: Ab initio molecular dynamics calculations on a carbonate-silicate-metal melt were performed to study speciation and coordination changes as a function of pressure and temperature. We examine in detail the bond abundances of specific element pairs and the distribution of coordination environments over conditions spanning Earth's present-day mantle. Average coordination numbers increase continuously from 4 to 8 for Fe and Mg, from 4 to 6 for Si, and from 2 to 4 for C from 1 to 148 GPa (4,000 K). Speciation acros… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Recent first principles/ab initio molecular dynamics and density functional theory (DFT) simulations have been used to gain further insights on how volatile elements are distributed among cores, magmas, and atmospheres. For example (Solomatova and Caracas, 2019;Davis, et al, 2022), found C coordination in silicate melts to be largely pressure dependent, implying that terrestrial magma oceans could have contained oxidized carbon polymers. The latter study also found strong clustering between C and Fe, which increases as a function of pressure, suggesting C could be present in cores.…”
Section: Figure 12mentioning
confidence: 99%
“…Recent first principles/ab initio molecular dynamics and density functional theory (DFT) simulations have been used to gain further insights on how volatile elements are distributed among cores, magmas, and atmospheres. For example (Solomatova and Caracas, 2019;Davis, et al, 2022), found C coordination in silicate melts to be largely pressure dependent, implying that terrestrial magma oceans could have contained oxidized carbon polymers. The latter study also found strong clustering between C and Fe, which increases as a function of pressure, suggesting C could be present in cores.…”
Section: Figure 12mentioning
confidence: 99%